Relatos de vida de habitantes de calle de la ciudad Armenia, Quindío (2023)
Therefore, in order to describe the life experiences of street dwellers in the city of Armenia, Quindío, from their life stories, a phenomenological study was carried out with 2 participants who are beneficiaries of a social foundation.